Advanced Practice Nursing: its implementation in Mexico and contribution to Primary Health Care - Sarmiento Luna, Flor Beatriz (2025)
Advanced Practice Nursing is a profile that contributes to the Primary Health Care strategy, in addition to being an area of opportunity for nursing professionals to work in different contexts with expanded skills, in order to improve health care and impact people's quality of life. In Mexico, the Health Care Model for Well-being (MAS-Bienestar) has been implemented since 2022 as part of the Strategic Health Program for Well-being, which aims to provide free health services, medicines and other associated supplies in the Health System for Well-being, which health care. Likewise, the “House to House Health” program was started, where health professionals will go to homes to follow up on the elderly and people witn disabilities. Therefore, incorporating advanced practice nursing Will improve care, due to the expandded role it plays and its ability to address health problems from disease prevention and health promotion.